Nearly 200 years of sustained selection have not overcome the leaf area–stem size relationship in the poinsettia. (16th May 2018) - Trejo, Laura; Rosell, Julieta A.; Olson, Mark E.
Abstract: Organismal parts often covary in their proportions, a phenomenon known as allometry. One way of exploring the causes of widespread allometric patterns is with artificial selection, to test whether or not it is possible to move populations into "empty" allometric space not occupied by the wild type. Domesticated organisms have been subject to many generations of selection, making them ideal model systems. We used the domesticated Christmas poinsettia Euphorbia pulcherrima in combination with wild populations to examine the origin of the proportionality between leaf area and stem size, which scales predictably across nearly all plants. In accordance with the stated aims of breeders to produce more compact plants, we predicted that domesticated poinsettias would have greater leaf area for a given stem volume than the tall, lanky wild ancestors. Our data rejected this prediction, showing instead that domesticates have leaf area–stem volume relationships identical to the wild ancestors. Presumably the metabolic dependence between stems and leaves makes the leaf area–stem volume relationship difficult to overcome. The relative fixity of this relationship leads to predictable covariation in other traits: The fuller outlines of domestic poinsettias involve significantly shorter internodes, and given a constant leaf area–stem volume relationship, smaller individual leaf areas. At the same time, domestic poinsettias are subject to selection favoring breakage resistance, which is achieved via thicker stems for a given length rather than stiffer stem tissue resistance to bending. Our results show that domesticated poinsettias differ from wild plants in a suite of traits including leaf size, internode distances, and stem length–diameter relations, but despite over 200 years of selection favoring rounded outlines, there has been no change in the total leaf area–stem volume relationship, helping to predict which changes are likely achievable and which will not be under continued artificial selection and in the wild.